ANALYSIS OF BLOOD COCKLE SHELL CONTENT AS A BIOCOMPOSITE MATERIAL ON ULTISOL SOIL - Sari Rahmiati; Yopy Mardiansyah; Vitri Aprilla Handayani; Moh. Arafat Wasiru (Jurusan Kimia FMIPA Universitas Lampung, 2024)
This research used blood cockle shells (Anadara granosa) originating from consumption waste in the Batam City area. Cockle shell samples were taken and prepared for analysis of mineral content using the FTIR method, including CaCO3 and other minerals. The blood cockle shells were applied to ultisol soil in Batam City to improve its fertility. The shells were crushed into a fine powder, then mixed with ultisol soil with several treatments, including 0 grams (control), 10 grams, 20 grams, and 30 grams with a soil mass composition of 220 grams for each treatment. The mixture of soil and shell powder was stirred until homogeneous before being applied to mustard greens plants. Based on the research results, the addition of shell powder had an effect on the level of plant fertility. The experimental results carried out showed an effect on each treatment given. This is in line with statistical testing with analysis of variance, obtaining a sig. value of 0.037 < Î± = 5% (0.05), indicating a significant difference in treatment for each treatment.